Efektifitas Pendekatan Cognitive Behavioral Therapy (CBT) untuk Mengatasi Depresi: Array - Muhammad Rizky; Netrawati; Yeni Karneli (Citra Dharma Cindekia, 2022)
Depression is a mood disorder that affects the way a person feels, thinks, or behaves which can interfere with social functioning and other activities. Depression can be triggered by biological, psychosocial or environmental factors such as traumatic events. This study aims to determine the effectiveness of the cognitive behavioral therapy (CBT) approach to overcome depression. Writing is designed using the method of literature (library research). The result of this approach is that all the literature reveals consistent results, that the cognitive behavioral therapy (CBT) approach is effective for dealing with depression. There are many studies showing that CBT is an effective therapy for treating depressive symptoms. Some literature also suggests that in treating depressive symptoms, CBT is comparable to the effects of medical drug therapy.